2000
DOI: 10.1523/jneurosci.20-03-01036.2000
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Influences Injury-Induced Microglial Migration and Accumulation in the Leech CNS

Abstract: Damage to the leech or mammalian CNS increases nitric oxide (NO) production and causes accumulation of phagocytic microglial cells at the injury site. The aim of this study was to determine whether NO plays a role in microglial migration and accumulation at lesions in which NO is generated by a rapidly appearing endothelial nitric oxide synthase (eNOS) in leeches. Immunohistochemistry and cytochemistry demonstrated active eNOS before and throughout the period of microglial accumulation at the lesion. Decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 39 publications
2
65
0
Order By: Relevance
“…NO has been shown to have opposing and complex effects on chemotactic responses exerted by various stimuli. For example, it has been shown that NO enhances chemotactic responses in some cell types (45,46,(61)(62)(63) upon certain stimuli, while inhibiting cell migration in others (47,64). Furthermore, NO has been shown to modulate T cell chemotaxis in Peyer's patches and in the nonlymphoid region of the intestine (65).…”
Section: Discussionmentioning
confidence: 99%
“…NO has been shown to have opposing and complex effects on chemotactic responses exerted by various stimuli. For example, it has been shown that NO enhances chemotactic responses in some cell types (45,46,(61)(62)(63) upon certain stimuli, while inhibiting cell migration in others (47,64). Furthermore, NO has been shown to modulate T cell chemotaxis in Peyer's patches and in the nonlymphoid region of the intestine (65).…”
Section: Discussionmentioning
confidence: 99%
“…When the leech nerve cord is injured, microglia migrate towards the lesion and accumulate at the damage site (145,482,556,970). In response to injury, leech connective glia and some microglia express endothelial nitric oxide synthase (eNOS) as revealed by immunolabeling.…”
Section: Evolutionary Origins Of Microgliamentioning
confidence: 99%
“…The NO could mediate the accumulation of microglia at the lesion site in the leech: a NOS inhibitor significantly reduced microglial accumulation. The nitric oxide (NO) donor spermine NONOate also inhibited accumulation, reduced average microglial migratory speed, and even reversibly arrested cell movement, indicating that NO is a stop signal for microglia and results in accumulation (145). NO's action on the migratory behavior of leech microglia may be mediated by cGMP (228).…”
Section: Evolutionary Origins Of Microgliamentioning
confidence: 99%
“…Previous studies reported that both the gaseous messenger molecule nitric oxide (NO) [2][3][4] and widely studied axon guidance/migration cues such as Netrins [5,6] regulated the migratory behavior of cells in the nervous system. However, little is known about whether there is any crosstalk between NO and guidance/migration cues during neural cell migration and accumulation.…”
Section: Dear Editormentioning
confidence: 99%